Kesalahan Pemahaman Konsep Peserta Didik dalam Menyelesaikan Soal-Soal Integral Lipat Dua pada Koordinat Polar - Rahma Siska Utari; Liana Septy; Lusinda Hutauruk (Jurnal Inovasi Matematika, 2021)
This research was a qualitative descriptive study to analyze the misunderstanding of students' concepts in solving two fold integral problems on polar coordinates. The 30 students who took the multivariable calculus course became the subjects in this study. Data were collected using tests and documentation. The results of the student's test answers and the documentation of students answers were corrected, analyzed based on indicators of conceptual understanding and data displayed. Analysis of students' answer errors based on indicators of concept understanding, namely (1) restating the integral concept. (2) representing the concept in other forms, (3) selecting and using procedures and (4) using problem solving concepts and algorithms. In restating the integral concept, students directly use the upper and lower limits of integration without writing down the integration results first. The mistake of representing the function to the graph is that the function is immediately sketched without creating a table, plotting points and creating curves. Errors in selecting and using procedures and using problem solving algorithms are due to students' lack of prior knowledge of prerequisite materials, namely trigonometric integrals and trigonometric functions.